Preparation of Cross-linked Starch Microparticles by a Water-in-oil Emulsion Solvent Diffusion Method for Use as Drug Delivery Carriers - Phromsopha, T.; Srihanam, P.; Baimark, Y. (Asian Journal of Chemistry, 2011)
Cross-linked starch microparticles containing model drug were prepared via a water-in-oil emulsion solvent diffusion method. Aqueous cross-linked starch solution and emulsifier mixture in ethyl acetate were used as water and oil phases, respectively. Sodium trimetaphosphate and methylene blue was used as cross-linker and water soluble model drug, respectively. The starch microparticles prepared with different starch/methylene blue and starch/sodium trimetaphosphate ratios resulted in nearly spherical in shape with fine dispersibility. From in vitro release test, the cross-linked starch microparticles showed sustainable release profiles. Cumulative drug released from starch microparticles decreased as decreasing of methylene blue ratio and increasing of sodium trimetaphosphate ratio.